Macromechanical modelling of cosserat elastic and visco-elastic media - Erofeev, Vladimir Ivanovich; Kazhaev, Vladimir Vladimirovich; Semerikova, Nadezhda Petrovna (Computational Continuum Mechanics, 2009)
It is shown that the dynamics of a Cosserat continuum (a micropolar medium) can be modeled as a motion of two rods interacting elastically or visco-elastically. The relation between the elasticity constants of the Cosserat medium and the initial parameters of the rods has been established. For the first time a visco-elastic operator has been introduced in the model of a micro-polar medium.